2015
DOI: 10.3384/diss.diva-117895
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Disease Mechanisms Diarrhea, Vomiting and Inflammation : How and Why

Abstract: Rotavirus infections cause diarrhea and vomiting that can lead to severe dehydration. Despite extensive tissue damage and cell death, the inflammatory response is very limited. The focus of this thesis was to study pathophysiological mechanisms behind diarrhea and vomiting during rotavirus infection and also to investigate the mechanism behind the limited inflammatory response. An important discovery in this thesis was that rotavirus infection and the rotavirus toxin NSP4 stimulate release of the neurotransmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 96 publications
(155 reference statements)
1
4
0
2
Order By: Relevance
“…This study showed that vomiting was significantly associated with Rotavirus infection, which is similar to the previous studies done in pre-vaccine era in rural Western Kenya, Northwestern Angola, Accra, Ghana, urban Bangladesh and which ultimately induces vomiting reflex, nausea and vomiting [18]. This study has found that vaccinated children indwelling with three or more fellow children in the same house are significantly more likely to acquire Rotavirus infection compared to those indwelling with less than three fellow children.…”
Section: Discussionsupporting
confidence: 88%
“…This study showed that vomiting was significantly associated with Rotavirus infection, which is similar to the previous studies done in pre-vaccine era in rural Western Kenya, Northwestern Angola, Accra, Ghana, urban Bangladesh and which ultimately induces vomiting reflex, nausea and vomiting [18]. This study has found that vaccinated children indwelling with three or more fellow children in the same house are significantly more likely to acquire Rotavirus infection compared to those indwelling with less than three fellow children.…”
Section: Discussionsupporting
confidence: 88%
“…Although early studies implicated VP7 in the cell entry process, subsequent studies increasingly have indicated that VP4 is the major player in Veterinary Medicine International this process. VP4 is susceptible to proteolysis and viral infectivity is increased several folds when VP4 is proteolytically cleaved and facilitates virus entry into cells [22]. During proteolysis, VP4 is cleaved into VP8 * (amino acids 1 to 247) and VP5 * (amino acids 248 to 776), and the cleavage products remain associated with the virion [30].…”
Section: Proteinsmentioning
confidence: 99%
“…Finally, the higher intraenterocyte calcium concentration causes enterocytes to die by oncosis. e rate of death of the mature villous tip enterocytes exceeds the rate of growth of immature enterocytes that are regenerated from the stem cells in the crypt, causing villous blunting and thus malabsorption [22]. Infection resolves both as the virus runs Veterinary Medicine International out of susceptible mature enterocytes and an immune response is generated [69].…”
Section: Pathogenesis Of Rotavirus Infectionmentioning
confidence: 99%
“…Infected children may also have a cough and runny nose. 8,9,10,11,12,13 Generally, reinfections are common in Rotavirus disease. 14 Immunity develops with each infection, so subsequent infections are less severe; adults are rarely affected.…”
Section: Introductionmentioning
confidence: 99%